Black Beauty - Sewell, Anna; Adapted by Sykes, Julie; Illustrated by Ball, Natalie (Oxford Oxford University Press, 2014)
'Black Beauty' is the autobiography of a horse, who narrates the amazing story of his life. See Black Beauty grow up and leave home to become a working horse doing different jobs for many owners - some kind and some cruel.
Include Illustrations.
English Fiction.